Analyzing Potentials and Barriers in Supply Chain Management in The Promise of Blockchain - Sinniati Sinniati; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
This study explored the potentials and barriers to the implementation of blockchain technology in supply chain management (SCM). The purpose of the research was to determine the potential of implementing blockchain technology to enhance SCM performance, identify the challenges faced in implementing blockchain in SCM, and understand the constraints and obstacles that needed to be overcome for successful implementation. The research method applied was a Systematic Literature Review (SLR) using the PRISMA Protocol, with 73 papers collected from 2018 to June 2023. Data analysis was conducted through Meta-Synthesis. The findings provided insights into the theoretical, policy, and managerial implications of implementing blockchain technology in SCM, contributing to the advancement of knowledge in this field.